2016
DOI: 10.1089/jamp.2015.1250
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Dose Estimation of Aerosol Delivery to Non-Human Primates

Abstract: Background: In pre-clinical animal studies the uniformity of dosing across subjects and routes of administration is a crucial requirement. In preparation for a study in which aerosolized live-attenuated measles virus vaccine was administered to cynomolgus monkeys (Macaca fascicularis) by inhalation, we assessed the percentage of a nebulized dose inhaled under varying conditions. Methods: Drug delivery varies with breathing parameters therefore we determined macaque breathing patterns (tidal volume, breathing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…After completion of ferret experiments, cynomolgus macaques were inoculated with 10 9 PFU rMVA-GFP by IM injection or aerosol (AER) inhalation 24 26 . Slices from either the hind leg muscle or lungs obtained from non-human primates at necropsy 6 HPA were analysed by direct CLSM, which revealed presence of GFP + cells after IM injection or AER inhalation, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After completion of ferret experiments, cynomolgus macaques were inoculated with 10 9 PFU rMVA-GFP by IM injection or aerosol (AER) inhalation 24 26 . Slices from either the hind leg muscle or lungs obtained from non-human primates at necropsy 6 HPA were analysed by direct CLSM, which revealed presence of GFP + cells after IM injection or AER inhalation, respectively (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the in vivo model does not enable control of breathing pattern which may differ in the lightly sedated animals as compared to patients. However, recent data indicate that in terms of milliliter per kilogram of body weight of tidal volume, macaques represent a relevant human model . Those potential limitations related to breathing patterns mainly apply to the absolute values of aerosol lung deposition reported, which may be slightly different in patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent data indicate that in terms of milliliter per kilogram of body weight of tidal volume, macaques represent a relevant human model. 25 Those potential limitations related to breathing patterns mainly apply to the absolute values of aerosol lung deposition reported, which may be slightly different in patients. However, as breathing patterns set on the in vitro model and animal experimental conditions were strictly equal in all experiments, differences observed between aerosol delivery conditions (i.e., comparison between vibrating mesh nebulization within the NHF circuit and control jet nebulization) may not have been affected by breathing pattern changes.…”
Section: Discussionmentioning
confidence: 99%
“…Bhasyham et al [12] showed that aerosol output dose increased from 18.6% with a tidal volume of 150 ml to 25.4% with a tidal volume of 300 ml during simulated HFNT. El Taoum et al [40] evaluated the delivery of aerosols via the nasal route with face masks in a 7-month and a 5-year-old head [41] showed that variation in tidal volume was the most important determinant for aerosol delivery to non-human primates. It is noteworthy that tidal volume was the parameter with the least effect during an adult breathing pattern, but had the greatest effect in small child and infant breathing.…”
Section: Influence Of Tidal Volume On Tracheal Dosementioning
confidence: 99%